Navigating digital tourism governance: a case study of branding strategies in the Mandalika special economic zones - Zitri, Ilham; Rifaid, Rifaid; Lestanata, Yudhi; Kurniawan, Cahyadi (Department of Government Studies Universitas Muhammadiyah Makassar, 2024)
The purpose of this research is to analyze how digital Tourism on Branding the Mandalika Special Region in West Nusa Tenggara; this investigation uses a descriptive methodology combined with a qualitative approach, as well as previously published literature and online news sources as well as secondary data obtained from related agencies. Most importantly, take advantage of the Nvivo 12 plus program to analyze the data results. The findings of this study indicate that the use of information and communication technology to promote Special Economic Zones through digital tourism, utilizing platforms such as websites, YouTube, Facebook, TikTok, Instagram, and the West Nusa Tenggara Tourism Office website, is a viable strategy for increasing tourism. Indonesian tourism industry. ITDC and National Council of Special Economic Zones websites. Government Regulation Number 52 of 2014 identifies two main focus topics, namely tourism areas and special economic areas, and prioritizes several initiatives. Development management in accordance with statutory regulations. PP Number 40 of 2021 discusses three important things: human resources and infrastructure, two facilities, and SEZ convenience for three commercial organizations. The finding of human resources and infrastructure is considered to be the main driver for branding the Mandalika Special Economic Zone in this policy.